Quantitation of phenolic compunds of three varieties of sweet potato extracts - Mohd Amirul Rosli (2014)
Sweet potato (Ipomoea batatas) has received a broad attention because it is an important resource of food and there is an abundance of pharmacologically active ingredient in it. Three varieties of I. batatas which is commercially available at the Pasir Mas, Kelantan were studied to determine and to compare the Total Phenolic Content (TPC) and Total Flavonoid Content (TFC) in each varieties of I. batatas. This researched also was conducted to determine the best solvent for maximum TPC and TFC extraction from I. batatas roots. The determination of TPC and TFC in the I. batatas was conducted by using calorimetric method where the absorbance of solution mixture was determined by using UV-vis spectrophotometer. The TPC of I. batatas was calculated (the standard curve equation: y=0.022x-0.0117, r²=0.998) and expressed in mg of Gallic Acid Equivalent (GAE) / 70g of sample on dry weight basis. While, the TFC was calculated (the standard curve equation: y=0.056x-0.0584, r²=0.971) and was expressed in mg of Quercetin Equivalent (QE) / 70g of sample on dry weight basis. Among all varieties of I. batatas, highest TPC was observed in acetone extract of orange flesh and lowest TPC was observed in water extract of white peel. While, the highest TFC was observed in ethanol extract of orange peel and the lowest TFC was observed in water extract of purple peel. The result showed that I. batatas has moderately polar phenolic as acetone extract yield the maximum TPC and TFC in most of the extract. As the conclusion, it is inferred that orange coloured of I. batatas has more TPC and TFC than the white coloured and purple coloured of I. batatas.